The Role Of Social Media In The Most Prominent Fields Of Life And Its Problems - Firdaus Bayinat Basha Al Bajali, Abul (International Journal of Psychosocial Rehabilitation, 2022)
The study concluded that social media in particular has taken a large and important space in the most prominent fields of contemporary life, especially open-source social media, and as long as most aspects of human, natural and cosmic activity; It was worth studying all their aspects to clarify the position of Sharia and the law on them and their rulings on them. There is no doubt about the necessity and necessity of submitting them to their controls to ensure optimal benefit from them, as they are among the services that are indispensable in our contemporary time. Accordingly, this study dealt with the issue of social media through the following images: Social media in the most prominent areas of life and its problems. Topics related to the media today are among the topics worthy of study and care, as the media occupies a large and influential space in various fields of life. Perhaps social media is one of the most prominent types of media in terms of influence and importance, as it is based on transmitting news and information from the community to the community itself, to achieve one of the purposes of news, guidance or guidance through its various means such as clubs, forums, places of worship, social networks, newspapers and books. The media directed to a particular place, group, or segment of society is considered its social media, such as the media directed to the community of a particular city or a segment such as women, or a group such as the disabled. Whereas social media is of such vitality and importance; This topic has been allocated according to the requirements of the study. This study was based on the extrapolation of the issues in which the opinions of scholars varied according to the multiplicity of factors related to the edge, according to an applied analytical methodology.